A Preliminary Analysis of the Toponymy in and around the So-Called Jerusalem Corridor - Zadok, Ran (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2019)
This paper is essentially an analysis of the toponymy of 23 villages. They are located in the Jerusalem Corridor to the west of this city. This region is the northernmost part of the Judean hill country. The 23 villages contain no less than 516 microtoponyms which shed light on the geomorphology, flora, fauna and history of the region. The article contains two appendices: on thorn-bushes used as fences and on the region of Sakasene.